2015
DOI: 10.1038/ng.3367
|View full text |Cite
|
Sign up to set email alerts
|

A gene-based association method for mapping traits using reference transcriptome data

Abstract: Genome-wide association studies (GWAS) have identified thousands of variants robustly associated with complex traits. However, the biological mechanisms underlying these associations are, in general, not well understood. We propose a gene-based association method called PrediXcan that directly tests the molecular mechanisms through which genetic variation affects phenotype. The approach estimates the component of gene expression determined by an individual’s genetic profile and correlates the “imputed” gene ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
2,317
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,570 publications
(2,348 citation statements)
references
References 52 publications
26
2,317
4
1
Order By: Relevance
“…Therefore, it does not prove causality, similarly to all current methods. [7][8][9][10][11][12] In fact, if gene functions are often pleiotropic, for which we found some evidence in the current study, the assumption of independence between the instrument variable and the outcome of Mendelian randomization approaches is more likely to be violated. 34 Still, the inferences made here can potentially guide phenotypic studies of gene functions in model systems.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, it does not prove causality, similarly to all current methods. [7][8][9][10][11][12] In fact, if gene functions are often pleiotropic, for which we found some evidence in the current study, the assumption of independence between the instrument variable and the outcome of Mendelian randomization approaches is more likely to be violated. 34 Still, the inferences made here can potentially guide phenotypic studies of gene functions in model systems.…”
Section: Discussionmentioning
confidence: 77%
“…From a study using SMR, 13 we found support for 69.1% (47/68) of the reported gene-trait associations, and for a study using PrediXcan, 7 this number was 66.7% (6/9) ( Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…These spatiotemporal maps of gene activity and gene regulation will be instrumental in pinpointing the specific brain region(s) and critical periods where susceptibility genes influence GTS pathophysiology at the molecular level 198,199 . In parallel, collaborations in the field of neuro-imaging genetics (the largest example of which is the ENIGMA Consortium) will facilitate integration of GTS genetics with systems neuroscience to uncover underlying GTS biology at the neural circuit level 200,201 .…”
Section: Thoughts For Dougmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] In parallel, large-scale expression quantitative trail locus (eQTL) mapping studies in multiple human tissues have revealed a large number of genetic variants that affect gene expression [13][14][15][16][17][18][19] (reviewed by Albert and Kruglyak 20 ). Gene expression serves as an important intermediate cellular phenotype that affects complex diseases and traits, [21][22][23][24] and the functional effects of eQTLs provide another lens through which researchers can investigate molecular mechanisms. 9,[13][14][15][16][17][18][19][20][25][26][27] However, the underlying functional mechanisms of eQTLs are still largely unclear.…”
Section: Introductionmentioning
confidence: 99%